LC-MS/MS method for proline-glycine-proline and acetylated proline-glycine-proline in human plasma - Tiwary, Ekta; Berryhill, Taylor F; Wilson, Landon; Barnes, Stephen; Prasain, Jeevan K; Wells, J Michael (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2023)
The extracellular cellular matrix (ECM) maintains tissue structure and regulates signaling functions by continuous degradation and remodeling. Inflammation or other disease conditions activate proteases including matrix metalloproteinases (MMPs) that degrade ECM proteins and in particular generate fragments of collagen and elastin, some of which are biologically active ECM peptides or matrikines. Stepwise degradation of collagen by MMP 8, 9 and prolyl endopeptidase release the matrikine proline-glycine-proline (PGP) and its product acetyl-PGP (AcPGP). These peptides are considered as potential biomarkers and therapeutic targets for many disease conditions such as chronic lung disease, heart disease, and cancer. However, there is no published, validated method for the measurement of PGP and AcPGP in plasma and therefore, we developed a sensitive, selective and reliable, isotope dilution LC-multiple reaction monitoring MS method for their determination in human plasma. The chromatographic separation of PGP and AcPGP was achieved in 3 min using Jupiter column with a gradient consisting of acidified acetonitrile and water at a flow rate of 0.5 ml/min. The limit of detection (LOD) for PGP and AcPGP was 0.01 ng/ml and the limit of quantification (LOQ) was 0.05 ng/ml and 0.1 ng/ml, respectively. Precision and accuracy values for all analytes were within 20 % except for the lowest QC of 0.01 ng/ml. The mean extraction recoveries of these analytes were > 90 % using a Phenomenex Phree cartridge and the matrix effect was < 15 % for all the QCs for PGP and AcPGP except the lowest QC. The stability of PGP and AcPGP was > 90 % in several tested conditions including autosampler use, storage at −80 °C, and after 6 times freeze–thaw cycles. Using this method, we successfully extracted and determined PGP levels in human plasma from healthy and COPD subjects. Therefore, this method is suitable for quantification of these peptides in the clinical setting.